La psicoterapia delle psicosi e il riduzionismo biologico - Fargnoli, Francesco (Il sogno della farfalla, 2016)
The last decades have witnessed a crisis in both organicist and psychogenetic theories in relation to the etiology of psychosis. The formulation of the multifactorial etiopathogenetic theory represents an attempt to overcome this crisis by proposing, however, a simple addition of two points of view without offering a real solution to the problem. In this paper the author highlights how, instead, the methodological and scientific leap contained in Massimo Fagioli’s theory can bring together research into human reality and studies into biological reality.